Histoire de l’art et anthropologie ou la définition complexe d’un champ d’étude - Cécile Voyer (L'Atelier du CRH)
As a consequence of its own history, the discipline devoted to the study of art has established complex links with the other social sciences. To tackle the anthropology of images in the field of medieval research first requires a statement of the anthropological approach to visual works. The experimental theoretical frameworks used to analyze the images of modern and contemporary periods are only partially relevant for the Middle Ages. Today, given the lack of an actual theory, a certain number of medievalists have adopted an approach of anthropological questioning in order to study visual works. In order to create a base for the study of the anthropology of medieval images, we must reflect on the symbolic effectiveness of the images, their substance and their materiality, in a contextual methodology.